Impact of SMOFlipid emulsion integration in total parenteral nutrition on inpatient outcomes and economic burden for preterm neonates: a retrospective cohort study - Mohamed Emad Eldin Refaay; Omaima Gaber Yassine; Ghada Ahmed Abu-Sheasha; Adel Zaki (BMC Pediatrics)
Abstract Introduction The use of lipid emulsion in TPN for preterm infants can affect clinical outcomes. Objective To assess the potential beneficial health outcomes and economic impact of including SMOFlipid emulsion in TPN for preterm infants, specifically focusing on the incidence of neonatal sepsis, LOS in the NICU, and the associated economic implications from the perspective of healthcare providers in Egypt. Methods A record-based retrospective cohort study was conducted in 2021. We collected data from the neonatal intensive care unit (NICU) of Alexandria University Pediatric Hospital, Egypt, for newborns who received TPN. The collected data included gestational age, birth weight, sex, diagnosis of sepsis, LOS in the NICU and type of TPN. Our sample consisted of 103 newborns who received TPN with SMOFlipid and 104 newborns who received TPN without SMOFlipid. Using the propensity score, the study groups’ baseline characteristics were balanced. Odds ratios were estimated using logistic regression, and the statistical significance was set at < 0.05. Results Compared to TPN without lipids, the use of SMOFlipid was associated with an observed reduction in the risk of sepsis (OR = 0.64, 95% CI: 0.272–1.51), as well as a difference in the mean reduction in hospital stay (4.12 days, p = 0.08). Furthermore, using SMOFlipid was associated with a significant mean reduction in cost of 6,396 EGP (95% CI: 1,491–11,546 EGP). Conclusion The integration of SMOFlipid into TPN for preterm infants is associated with decreased incidence of sepsis, reduced NICU stay, and significant cost savings, warranting consideration for standard care practices.